Revisited and innovative perspectives of oral ulcer: from biological specificity to local treatment - Pan, Ziyi; Zhang, Xu; Xie, Wangni; Cui, Jing; Wang, Yue; Zhang, Boya; Du, Liuyi; Zhai, Wenhao; Sun, Hongchen; Li, Yunfeng; Li, Daowei (Frontiers in Bioengineering and Biotechnology, 2024)
Mouth ulcers, a highly prevalent ailment affecting the oral mucosa, leading to pain and discomfort, significantly impacting the patient's daily life. The development of innovative approaches for oral ulcer treatment is of great importance. Moreover, a deeper and more comprehensive understanding of mouth ulcers will facilitate the development of innovative therapeutic strategies. The oral environment possesses distinct traits as it serves as the gateway to the digestive and respiratory systems. The permeability of various epithelial layers can influence drug absorption. Moreover, oral mucosal injuries exhibit distinct healing patterns compared to cutaneous lesions, influenced by various inherent and extrinsic factors. Furthermore, the moist and dynamic oral environment, influenced by saliva and daily physiological functions like chewing and speaking, presents additional challenges in local therapy. Also, suitable mucosal adhesion materials are crucial to alleviate pain and promote healing process. To this end, the review comprehensively examines the anatomical and structural aspects of the oral cavity, elucidates the healing mechanisms of oral ulcers, explores the factors contributing to scar-free healing in the oral mucosa, and investigates the application of mucosal adhesive materials as drug delivery systems. This endeavor seeks to offer novel insights and perspectives for the treatment of oral ulcers.